2021
DOI: 10.1101/lm.053472.121
|View full text |Cite
|
Sign up to set email alerts
|

Maintained goal-directed control with overtraining on ratio schedules

Abstract: It is thought that goal-directed control of actions weakens or becomes masked by habits over time. We tested the opposing hypothesis that goal-directed control becomes stronger over time, and that this growth is modulated by the overall action–outcome contiguity. Despite group differences in action–outcome contiguity early in training, rats trained under random and fixed ratio schedules showed equivalent goal-directed control of lever pressing that appeared to grow over time. We confirmed that goal-directed co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 32 publications
3
11
0
Order By: Relevance
“…However, as we have shown, overtraining may in fact not install stimulus-driven processes but instead strong goal-directed processes. This is in line with recent work, which has shown that overtraining leads to strong goal-directed processes in rodents (Garr et al, 2021). Moreover, strong goal-directed processes have also been invoked to explain addictive behaviors (Hogarth, 2020).…”
Section: Discussionsupporting
confidence: 93%
“…However, as we have shown, overtraining may in fact not install stimulus-driven processes but instead strong goal-directed processes. This is in line with recent work, which has shown that overtraining leads to strong goal-directed processes in rodents (Garr et al, 2021). Moreover, strong goal-directed processes have also been invoked to explain addictive behaviors (Hogarth, 2020).…”
Section: Discussionsupporting
confidence: 93%
“…Indeed, some studies found that sensitivity to outcome devaluation depends on the amount of training (Adams, 1982;Hardwick et al, 2019;Tricomi et al, 2009), which has been taken as evidence for the idea that overtraining of operant conditioning installs habitual processes. Note, however, that other studies found that behavior was still sensitive after overtraining, thereby providing evidence for goal-directed processes even after overtraining (de Wit et al, 2018;Garr et al, 2021;LaFlamme et al, 2022;Pool et al, 2022).…”
Section: Discussionmentioning
confidence: 82%
“…Note, however, that other studies found that behavior was still sensitive after overtraining, thereby providing evidence for goal-directed processes even after overtraining (de Wit et al, 2018;Garr et al, 2021;LaFlamme et al, 2022;Pool et al, 2022).…”
Section: Discussionmentioning
confidence: 82%